Highly Stretchable Patterned Gold Electrodes Made of Au Nanosheets. (9th April 2013) - Moon, Geon Dae; Lim, Guh‐Hwan; Song, Jun Hyuk; Shin, Minkwan; Yu, Taekyung; Lim, Byungkwon; Jeong, Unyong
<x xml:space="preserve">Abstract</x> Multilayered Au nanosheets are suggested as a novel class of material for fabricating stretchable electrodes suitable for organic‐based electronic devices. The electrodes show no difference in resistivity during repeated stretching cycles of up to ϵ = 40%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>